ANALISIS PERBANDINGAN EFISIENSI BANK PEMERINTAH (BUMN) DAN BANK SWASTA DI INDONESIA PERIODE 2015-2019 - Kadirisman, Indra (PRIMA EKONOMIKA, 2021)
This study aims to determine the results of a comparative analysis of the level of efficiency of state-owned banks with private banks in Indonesia during the 2015-2019 period. The design of this research is comparative quantitative. The study population includes Conventional Commercial Banks Listed on the Indonesia Stock Exchange during the observation period 2015-2019. The sample selection technique used purposive sampling method by taking a sample of 4 government banks (BUMN) and 4 private banks. The measurement of efficiency in this study uses the Data Envelopment Analysis (DEA) method with the Banxia Frontier Analysis (BFA) computer program. The input variables used in the study are Capital, Total Assets and Personnel Costs, while the output variable is Operating Profit. To determine the efficiency comparison between state-owned banks (BUMN) and private banks, this study used the Mann Whitney U-test non-parametric difference test. The results of the research with the BFA show that in the 8 banks that were used as research samples, there were two banks that were declared efficient with an average value of 100% and 2 banks were declared inefficient with an average value of <100% during 2015-2019, representing the Government Bank group. . Meanwhile, in the private bank group, there were two banks that were declared efficient with an average value of 100% and 2 banks were declared inefficient with an average value of <100% during 2015-2019. While the results of the Mann Whitney U-test difference test show that there is no significant difference between the efficiency of state-owned banks (BUMN) and private banks during the 2015-2019 period by looking at the sig value. (2-tailed) 0.741> 0.05. Keywords : efficiency; data envelopment analysis (DEA); input; output